From parliamentary pay to party funding: the acceptability of informal institutions in advanced democracies - Bolleyer, Nicole; Trumm, Siim (Wiley, 2014)
While direct state funding of political parties has been a prominent theme in cross-national research over the last decade, we still know little about party strategies to access state resources that are not explicitly earmarked for partisan usage. This paper looks at one widespread but often overlooked informal party practice: the ‘taxing’ of MP salaries, i.e., the regular transfer of fixed salary shares to party coffers. Building on notions of informal institutions developed in work on new democracies, our theoretical approach specifies factors that shape the acceptability of this legally non-enforceable intra-organisational practice. It is tested through a selection model applied to a unique data set covering 124 parties across 19 advanced democracies. Controlling for a range of party- and institutional-level variables, we find that the presence of a taxing rule and the collection of demanding tax shares are more common in leftist parties (high internal acceptability) and in systems in which the penetration of state institutions by political parties is intense (high external acceptability).